PERBANDINGAN KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH FISIKA BERDASARKAN MULTIREPRESENTASI - Ayu Lestari, Hasnawati; Werdhiana, I Komang (Universitas Tadulako, 2021)
This study aims to determine the comparison of students' abilities in solving physics problems based on multiple representations. This research is a qualitative descriptive study. This research was conducted at Man Insan Cendekia Palu City in the 2019/2020 academic year. The subjects in this study were 15 students of class X IPA Asy-Syams Man IC Palu City. The test consists of 4 multi-representation questions, namely verbal representations, pictures, graphs and mathematical representations. The results showed that the comparison of students' ability to solve physics problems based on multi-representations, obtained an average percentage of 45.33% (enough) for verbal representation, image representation of 58.16% (enough), graphic representation of 66.46% ( good), and mathematical representation of 74.33% (good). Based on the average percentage of each representation, the highest representation of the three representations is the mathematical representation. Based on the interviews, respondents said that solving problems in mathematical form was easier. Meanwhile the lowest representation was verbal representation. Students thought that verbal representation questions are the most difficult to understand because students are unable to find or identify information in the form of words alone.